COMMODITY POLICY AS AN IMPORTANT COMPONENT OF THE COMPANY’S MARKETING ACTIVITY - BOIKO, Ruslan; ANDRUSHKEVYCH, Zinayida; NIANKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article highlights the main problems of application of commodity policy as one of the most important components of the enterprise marketing complex. The works of scientists who were engaged in the study of these issues are analyzed, insufficiently studied aspects are highlighted. It is noted that an effective product strategy is key in the marketing strategy as a whole. Attention is focused on the fact that the features of the enterprise’s products determine a set of marketing tools, so the development of a commodity (product) strategy in modern conditions is extremely relevant. A set of understandings of the definition of «policy» as an instrument of economic activity of enterprise is analyzed. It is noted that in the conditions of marketing orientation of the enterprise, the main task is to determine the type of products and production volumes, as well as when, how and for whom these products will be produced. It is concluded that clear and balanced marketing activity is a competitive advantage of the enterprise. Various definitions of the definition of «commodity policy» by domestic scientists are considered. It is determined that commodity policy is a set of managerial decisions that contributes to the development of an optimal product range, maintaining the competitiveness of a product at the appropriate level and bringing it to the market. The one-sidedness of this approach is noted. The main goals of the commodity policy of enterprise are defined. It is concluded that during the formation of the commodity policy of enterprise, the use of a strategic approach will provide an opportunity to reduce costs, strengthen competitiveness in the market, find potential for effective commercial and economic activity, meet consumer needs and make a profit. It was concluded that the development and implementation of trade marketing tools in the activities of a retail trade institution will contribute to retaining existing customers and attracting new ones, stimulating buyers to make repeat purchases, forming emotional attachment and customer loyalty to the institution, improving the advertising and communication policy of the institution, increasing sales.